Untargeted metabolomics based on HS- SPME-GC-MS revealing the dynamic evolution of aroma components during cigar aging - Yang, Mingxuan; Zhou, Huina; Hu, Xi; Liu, Xiangyu; Lei, Jinshan; Ye, Keyuan; Zhou, Ting; Hu, Jun; He, Baojiang (Frontiers in Plant Science, 2025)
Cigar aging plays a critical role in enhancing flavor complexity and overall quality of cigar. In this study, an untargeted metabolomics method based on headspace solid-phase microextraction coupled with gas chromatography–mass spectrometry (HS-SPME-GC-MS) was used to comprehensively profile volatile compounds and track their dynamic changes during aging. A total of 1,836 volatile compounds were identified, primarily comprising heterocyclics, terpenoids, ketones, and esters. Multivariate analyses, including principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA), segmented the aging process into four distinct stages, with most differential metabolites showing upregulated trends. Notably, terpenoids exhibited substantial increases in both diversity and abundance. KEGG pathway enrichment analysis highlighted significant involvement of sesquiterpenoid and triterpenoid biosynthesis pathways in cigar aging process. Analysis based on relative odor activity values (rOAV) indicated a progressive enhancement of fruity, floral, honey, woody, and sweet notes, while coffee, roasted, hay, burnt, and spicy aromas declined over time. By integrating rOAV data with K-means clustering analysis, 21 key aroma-active compounds were identified to be closely associated with the aroma changes during aging, including 14 consistently upregulated compounds (e.g., (E)-β-damascone, δ-cadinene) and 7 downregulated ones (e.g., 2-ethyl-3,5-dimethylpyrazine, 3-octen-2-one). These findings provide new insights into the metabolic basis of cigar aging and offer a scientific foundation for optimizing industrial aging processes.